PENTINGNYA LAPORAN KEUANGAN UNTUK MENILAI KINERJA KEUANGAN PERUSAHAAN - Helmi Herawati (Universitas Prof.Hazairin,SH Bengkulu, 2019)
As for the purpose of this studi the importance of financial statements to assess company performance. Research has benefits for the company as input in the importance of a financial report in terms of assessing a company's performance to make a decision in the future. This research also benefits researchers to find out how important these financial statements are for evaluating performance. This study uses a Naturalistic method commonly referred to as a qualitative method, according to Sugiyono (1999: 8) is a study used to examine a natural object (as opposed to an experiment) where researchers are a key instrument. This study uses data qualitative, namely data formed by words, sentences or schemes and images. The source of this research data from secondary data, namely the data source is not directly through literature studies, notes and books that exist. Performance is financial performance is a description of the financial condition of a company in a certain period both concerning aspects of fund raising and fund distribution, which are usually measured by capital adequacy indicators, liquidity and profitability. The benefits of performance appraisal for management are to manage organizational operations, assist decision making, identify training and development needs of employees, provide feedback for employees how employers value their performance, provide a basis for distribution of awards